2019
DOI: 10.1183/13993003.01184-2018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pulmonary aspergillosis commonly complicates treated pulmonary tuberculosis with residual cavitation

Abstract: Chronic pulmonary aspergillosis (CPA) complicates treated pulmonary tuberculosis (TB), with high 5-year mortality. We measured CPA prevalence in this group.398 Ugandans with treated pulmonary TB underwent clinical assessment, chest radiography and Aspergillus-specific IgG measurement. 285 were resurveyed 2 years later, including computed tomography of the thorax in 73 with suspected CPA. CPA was diagnosed in patients without active TB who had raised Aspergillus-specific IgG, radiological features of CPA and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
188
6
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(221 citation statements)
references
References 31 publications
20
188
6
7
Order By: Relevance
“…Therefore, we calculated the prevalence rate of fungus ball as 18.0% in patients with old PTB. Several reports have also shown that CPA or and aspergilloma as a sequel to previous treated TB 1–5,10 . In concordance with Kosmidis and Denning 11 who suggested that the persistence of lung cavities in TB patients with previous successful treatment increase the rate of aspergilloma, in our study all patients with fungus balls had a history of previous treated PTB in a period of 2‐16 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, we calculated the prevalence rate of fungus ball as 18.0% in patients with old PTB. Several reports have also shown that CPA or and aspergilloma as a sequel to previous treated TB 1–5,10 . In concordance with Kosmidis and Denning 11 who suggested that the persistence of lung cavities in TB patients with previous successful treatment increase the rate of aspergilloma, in our study all patients with fungus balls had a history of previous treated PTB in a period of 2‐16 years.…”
Section: Discussionsupporting
confidence: 90%
“…However, Aspergillus species are considered as the most common cause of disease 3 . Scedosporium boydii , Fusarium species and the species related to Mucorales accounted for less than 5% in the occurrence of fungus ball 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently been published with serological data using only commercial ELISA tests for CPA diagnosis in an area with a high prevalence of tuberculosis [1, 13, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pulmonary aspergillosis (CPA) is a slow and progressive lung disease caused by Aspergillus spp. that develops in preexisting cavities of patients with chronic respiratory diseases, and pulmonary tuberculosis is its main predisposing factor, with a global prevalence estimated at 1.2 million cases [1]. I Its prognosis is poor, with 38-85% mortality in five years [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation